2019
DOI: 10.1111/jcmm.14230
|View full text |Cite
|
Sign up to set email alerts
|

SP/NK‐1R promotes gallbladder cancer cell proliferation and migration

Abstract: Aberrant substance P/neurokinin‐1 receptor (SP/NK‐1R) system activation plays a critical role in various disorders, however, little is known about the expression and the detailed molecular mechanism of the SP and NK‐1R in gallbladder cancer (GBC). In this study, we firstly analyzed the expression and clinical significance of them in patients with GBC. Then, cellular assays were performed to clarify their biological role in GBC cells. Moreover, we investigated the molecular mechanisms regulated by SP/NK‐1R. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
(91 reference statements)
2
31
0
Order By: Relevance
“…In tumor cells, SP through the NK-1R promotes an anti-apoptotic effect as well as proliferation, migration, invasion and metastasis ( Figure 1) [13,25,27,30,36,37]. Cancer cells express both SP and the NK-1R, and it seems that the undecapeptide is involved in an autocrine mechanism that promotes mitogenesis in tumor cells [13,21,28,[38][39][40][41][42][43][44].…”
Section: The Sp/nk-1r System and Cancer: Cell Signaling Pathways Ovementioning
confidence: 99%
See 3 more Smart Citations
“…In tumor cells, SP through the NK-1R promotes an anti-apoptotic effect as well as proliferation, migration, invasion and metastasis ( Figure 1) [13,25,27,30,36,37]. Cancer cells express both SP and the NK-1R, and it seems that the undecapeptide is involved in an autocrine mechanism that promotes mitogenesis in tumor cells [13,21,28,[38][39][40][41][42][43][44].…”
Section: The Sp/nk-1r System and Cancer: Cell Signaling Pathways Ovementioning
confidence: 99%
“…It is also important to note that the SP/NK-1R system is involved in the migration of cancer cells ( Figure 1) [36]. This mechanism is mediated by the Akt/NF-κB pathway: the undecapeptide increases tumor-associated cytokines and NF-κB p65 expression and decreases cancer cell proliferation/migration when a reduced activation of Akt/NF-κB occurs [36]. The SP/NK-1R system also controls membrane blebbing, a mechanism related to cell migration and spreading ( Figure 1) [27,36,57,58].…”
Section: The Sp/nk-1r System and Cancer: Cell Signaling Pathways Ovementioning
confidence: 99%
See 2 more Smart Citations
“…SP accelerates the migration of esophageal squamous cell carcinoma (in which the NK-1R is overexpressed) and enhances the expression of factors involved in angiogenesis via the overexpression of vascular endothelial growth factor receptor 1 and vascular endothelial growth factor A [56]. It has been reported that by reducing the activation of Akt or NF-κB, the migration of cancer cells was attenuated [50]. It is also known that the expression of the full-length isoform of the NK-1R reduced metastasis, whereas the activation of the truncated form increased it [57]; that SP promoted the migration of cancer cells by modulating the level of intracellular Ca ++ [58]; and that in metastatic tumors, an increase in SP/NK-1R staining occurred [30].…”
Section: Cancer and The Substance P/neurokinin-1 Receptor Systemmentioning
confidence: 99%